1998
DOI: 10.1002/(sici)1521-4141(199802)28:02<687::aid-immu687>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells, but not macrophages, produce IL-12 immediately following Leishmania donovani infection

Abstract: Infection with Leishmania, an obligate intracellular parasite of mononuclear phagocytes, stimulates the production of IFN-gamma from NK cells, via a pathway which is dependent upon IL-12 and IL-2. IL-12 is also essential for the development of host protective T cell responses to this parasite. However, previous in vitro studies have indicated that macrophages fail to make IL-12 following infection with Leishmania, and that subsequent to infection, macrophages become refractory to normal IL-12-inducing stimuli.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
176
0
8

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(193 citation statements)
references
References 32 publications
9
176
0
8
Order By: Relevance
“…3B, there was a 16-fold induction of IL-12p40 mRNA at 8 h of infection with promastigotes alone, but a less than 4-fold induction following infection with amastigotes. Notably, the expression levels in both groups dropped dramatically at 24 h post-infection, confirming the transient induction of IL-12p40 gene during Leishmania infection (Gorak et al, 1998). The levels of IL-12p35 mRNA were below the detection limit in DCs infected with parasites alone.…”
Section: Down-regulation Of Il-12 Production By La Parasites At Gene mentioning
confidence: 53%
See 2 more Smart Citations
“…3B, there was a 16-fold induction of IL-12p40 mRNA at 8 h of infection with promastigotes alone, but a less than 4-fold induction following infection with amastigotes. Notably, the expression levels in both groups dropped dramatically at 24 h post-infection, confirming the transient induction of IL-12p40 gene during Leishmania infection (Gorak et al, 1998). The levels of IL-12p35 mRNA were below the detection limit in DCs infected with parasites alone.…”
Section: Down-regulation Of Il-12 Production By La Parasites At Gene mentioning
confidence: 53%
“…Infection with L. major or L. donovani pro-or amastigotes, DCs can induce IL-12p40 production in vitro and in vivo (Bennett et al, 2001;Gorak et al, 1998;Konecny et al, 1999). However, we found that La promastigotes only weakly induced IL-12p40 production, whereas infection of amastigotes was devoid of this response (Fig.3B).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…MP are not the only cell type capable of producing of IL-12 and certainly it has been demonstrated that the in vivo source of IL-12 during Leishmania spp. infection is likely dendritic cells (Gorak et al, 1998;Marovich et al, 2000;McDowell et al, 2002). However, Leishmania spp.-infected dendritic cells require CD40L costimulation for IL-12 production (Marovich et al, 2000;McDowell et al, 2002), suggesting that during infection, dendritic cells initiate a protective response after interaction with antigenspecific T-cells in lymphoid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Early infection is accompanied by rapid IL-12 production by DC [12], the activation of CD4 + and CD8 + T cells, and the subsequent production of a variety of Th1 and Th2 cytokines, including IL-2, IFN-c and IL-4 [13,14]. While this immune response can readily eliminate most L. donovani amastigotes from the liver of infected mice over a 50-100-day period [15], parasites persist in the spleen, and this persistence is associated with severe splenomegaly and an array of pathological changes to the splenic lymphoid microenvironment [16][17][18].…”
Section: Introductionmentioning
confidence: 99%